2018
DOI: 10.1111/ppc.12296
|View full text |Cite
|
Sign up to set email alerts
|

Effect of university students’ sedentary behavior on stress, anxiety, and depression

Abstract: Intervention programs that reduce sedentary behavior and improve physical activity and mental health for university students are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
113
1
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(135 citation statements)
references
References 33 publications
(65 reference statements)
10
113
1
11
Order By: Relevance
“…This may at least be partly caused by the change in social tendencies and the development of habits leading to weight gain, stress, and anxiety [46,47,48]. This life period is, therefore, critical and the promotion of healthy habits in relation to nutrition and physical activity is necessary [49].…”
Section: Discussionmentioning
confidence: 99%
“…This may at least be partly caused by the change in social tendencies and the development of habits leading to weight gain, stress, and anxiety [46,47,48]. This life period is, therefore, critical and the promotion of healthy habits in relation to nutrition and physical activity is necessary [49].…”
Section: Discussionmentioning
confidence: 99%
“…Eleven studies showed 'mixed' findings between sedentary behaviour and stress. Firstly, both positive and null associations were found among nine studies (n=1 strong- [50]; n=2 moderate- [37,41]; n=6 weak-quality [33,38,42,46,49]). Stress was self-reported in eight of these studies [33,38,41,42,46,49,50], while one utilised objective measures (salivary cortisol) [37]).…”
Section: Combined Findingsmentioning
confidence: 98%
“…Specifically, a total of 19 studies (n= 2 strong-quality [50,51]; n=8 moderate-quality [34,35,37,41,44,48,52,53]; n=9 weak-quality [38,40,42,45,46,49,[54][55][56]) reported on associations between sitting time and stress. Five studies (n=1 strong-quality [51]; n=2 moderate-quality [34,35]; n=2 weak-quality [45,54]) found positive associations between sitting time and stress, i.e.…”
Section: Overall Sitting Timementioning
confidence: 99%
See 1 more Smart Citation
“…A study of seven universities in the UK showed high rates of binge and problem drinking (El Ansari et al, 2011), and a study in Hong Kong reported that relatively few university students engaged in any form of physical activity (31.2%) or regular exercise (13.8%; Lee & Loke, 2005). In South Korea, university students' time spent sitting is nearly twice that of U.S. students, and more than the daily average among adults in 20 countries (Lee & Kim, 2019). Among Korean college students, 10.8% of deaths are related to alcohol and more than half of university students experience alcohol‐related problems (Kim, Jang, & Jeong, 2006); 15.9% of South Korean university students use conventional cigarettes, 0.8% use e‐cigarettes, and 20.4% are dual users of conventional and e‐cigarettes (Jeon et al, 2016).…”
Section: Introductionmentioning
confidence: 99%